Case Report: A 65-year-old man with paraganglioma accompanied by elevated interleukin-6 levels and KIF1B single gene mutation - Wang, Chi; Guan, Ming; Zhang, Shuang; Cui, Can (Frontiers in Endocrinology, 2023)
Paraganglioma is a less prevalent disease, and paraganglioma with only secreting interleukin-6(IL-6) have not been reported. A 64-year-old male patient came to hospital with the chief complaints of fever and palpitations.The peak body temperature was 38.7°C (101.66°F). Heart rate was 110 bmp, while blood pressurewas in normal range. Antibiotics and antiviral therapies were ineffective. The levels of blood IL-6, c-reactive protein (CRP)，alkaline phosphatase(ALP), platelet（PLT）, glutamyltransferase(GGT), fibrinogen and D-Dimer were all elevated obviously. Infectious diseases, anto-immune diseases and hematological malignancy were all excluded. Nearly 10 years ago, a large retroperitoneal mass of the patient was detected in accident. Fortunately, there was no special symptoms for past ten years by follow-up regularly. After admission this time, the PET-CT were performed. A large confounding density mass at the upper part of abdominal and retroperitoneal was seen considered as the possibility of paraganglioma. Howerver, biochemical assays for blood and urine catecholamine and their metabolites including adrenaline, norepinephrine, 3-methoxytyramine, methoxyepinephrine, methoxynorepinephrinewere and vanillylmandelic acid were all in normal range in spite of mild elevated dopamine with no significance. The whole-exome capture and sequencing of the genomic DNA of the patient showed a heterozygous mutation in coding site of KIF1B gene (Coding: NM_015047.3:c.4660G >C, Mutation: p.Val1554Leu, chromosomal location It is chr1: 10428570). The mutation at this locus of KIF1B has not been reported previously. The patient refused the surgical treatment. Because the mass oppresses near the several important organs including pancereas, the risk of surgery was high. Then, doxazosin was administrated to the patient. After taking doxazosin, the symptoms released rapidly. Body temperature returned to normal range in 3 days. Heart rate decreased to about 90 bmp. In the followimg days, the levels of IL-6，CPR，ALP, platelet, GGT fibrinogen and D-Dime decreased by and by. After 63 days of doxazosin given, IL-6 levels was completely normal. After 190 days of medication, IL-6, hemoglobin (Hb) and GGT also fully returned to normal range. After onset of 1 year the patient had blood test once again. Almost all blood index were in normal range including IL-6.